DEFICIENCY OF VITAMIN D IS ASSOCIATED WITH FEMALE INFERTILITY - ASMIK G. Bochkarnikova; ALEXEY G. Trishkin; OLGA A. Pustotina; VADIM G. Mozes (Фундаментальная и клиническая медицина, 2018)
Aim. To determine the level of vitamin D in women with infertility in Kemerovo (Southwestern Siberia). Materials and Methods. We consecutively recruited 98 infertile women and 40 healthy women who applied for the routine examination in our medical center. Serum level of 25-hydroxyvitamin D (alternatively called calcifediol, calcidiol, or 25-hydroxycholecalciferol) was measured by chemiluminescent microparticle immunoassay. Results. Average levels of 25-hydroxyvitamin D in both groups were signficantly lower as compared to the reference values (21.79 ± 1.35 versus 28.03 ± 1.60 ng/mL, respectively, p = 0.001). Notably, women with infertility were more frequently diagnosed with an insufficiency/deficiency of 25-hydroxyvitamin D than healthy women (83.7% versus 60.0%, respectively, p = 0.003). Among these individuals, deficiency of 25-hydroxyvitamin D was more prevalent in infertile women in comparison with insufficiency (51.2% versus 48.8%, respectively), while the reverse was the case in healthy women (17.0% versus 83.0%, respectively).